Etiology of granulomatous lobular mastitis based on metagenomic next-generation sequencing. (December 2021) - Bi, Jiaxin; Li, Zhixin; Lin, Xiao; Li, Fang; Xu, Hua; Yu, Xuewen; Liu, Lingyun; Liang, Yingying; Xu, Zhouwen; Wang, Jiachuan; Shao, Mumin
Highlights: First study to perform next-generation sequencing in fresh mastitis samples Corynebacterium kroppenstedtii verified as a cause of granulomatous lobular mastitis Other unreported pathogens in granulomatous lobular mastitis identified Increased prolactin observed as another noteworthy factor Lipophilic antibiotics and prolactin inhibitor may have therapeutic prospects Abstract: Objectives: We aimed to comprehensively explore the etiology of granulomatous lobular mastitis (GLM) to optimize treatment programs. Methods: We collected 30 fresh mastitis samples for metagenomic next-generation sequencing, morphological observation, and analysis of the clinical information. Results: Of the 30 samples, 25 were GLM; pathogens were detected in 17, these were: Corynebacterium kroppenstedtii (10 of 25, 40%); C. kroppenstedtii and Pseudomonas oleovorans (3 of 25, 12%); C. kroppenstedtii and human gammaherpesvirus 4 (1 of 25, 4%); Acinetobacter baumannii and C. kroppenstedtii (1 of 25, 4%); P. oleovorans (1 of 25, 4%); and Tepidiphilus thermophilus (1 of 25, 4%). Abnormal sex hormone levels (mainly prolactin) and/or autoimmune function were found in 12 of the 25 samples. Lipophilic antibiotics (rifampicin) were found to work effectively in patients with slow-healing wounds after surgery. Conclusions: The main pathogenic factor of GLM is C. kroppenstedtii infection, but other unusual pathogens ( P. oleovorans, human gammaherpesvirus 4, A. baumannii, T. thermophilus ) are likely to be closely related to GLM, particularly human gammaherpesvirus 4 (Epstein-Barr virus)-associated mastitis, which may be a new entity of mastitis. Abnormal levels of sex hormones and autoimmune function are also common causes. Therefore, lipophilic antibiotics (rifampicin) and prolactin inhibitors may be an effective treatment.